2019
DOI: 10.3390/f10030242
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Concentration in Leaf Litter and Soil in Xishuangbanna Tropical Forests: Does Precipitation Limitation Matter?

Abstract: Tropical forests are generally expected to be limited by the availability of nitrogen (N) and phosphorus (P), and these nutrient limitations could be increased by changes in forest biogeochemistry due to limited precipitation. This effect is presumed to be enhanced in the forests predominated by monsoon climate. The present study examined the impacts of monthly precipitation on total N and P in leaf litter and soil of Xishuangbanna tropical forests. Litterfall and top soil were sampled from each of the five 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Forest plantation is expected to have a lower total P accumulated in the litter than natural forest, as found by Yang (2005). However, Mani and Cao (2019) also reported that the natural forest they studied had a higher total P which ranged from 600 to 700 mg kg -1 . Similarly, the control recorded a higher total P in the forest litter in the current study.…”
Section: Total Phosphorus In Forest Littermentioning
confidence: 77%
“…Forest plantation is expected to have a lower total P accumulated in the litter than natural forest, as found by Yang (2005). However, Mani and Cao (2019) also reported that the natural forest they studied had a higher total P which ranged from 600 to 700 mg kg -1 . Similarly, the control recorded a higher total P in the forest litter in the current study.…”
Section: Total Phosphorus In Forest Littermentioning
confidence: 77%
“…Second, close proximity of plants implied strong competition (Radtke et al ., 2003), so the zero distance between hemiepiphytes and their hosts suggests their intense competition. Third, P is commonly a limiting nutrient element in our study area (Han et al ., 2005; Mani & Cao, 2019) and other tropical ecosystems (Wright, 2019; Hou et al ., 2020), and competing for deficient soil nutrients is a widespread ecological process in plant communities (Baribault et al ., 2012; Carl et al ., 2018; Turner et al ., 2018). These reasons support the idea that against the background of P deficiency in tropics, P competition between hemiepiphytes and their hosts is a general phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A low P concentration in soil was also found in the medium-high land of Bangladesh (Rahman et al 2017). P is the most limiting nutrient, and since the low pH and P are positively related, therefore acidic soil can further decrease P availability (Uzoho and Oti 2004;Mani and Cao 2019).…”
Section: Tablementioning
confidence: 93%